Literatura e as relações étnico-raciais na escola: uma experiência de letramento literário em comunidades quilombolas - Costa, Nelzir Martins (2021)
Brazilian Society is composed of an ethnic diversity, however there is not an effective racial democracy, and this generates disadvantages for the African Brazilian population regarding the White Community, with daily occurrences of prejudice and racial discrimination. This research aimed to verify how the literary Reading of African Brazilian thematic books could contribute with the ethnical and racial discussions and the empowerment of black culture and identity in the school, mainly the works selected by the government Program titled Programa Nacional da Biblioteca da Escola (PNBE) of 2013. In order to do so, a collaborative research-action was carried out in two Quilombola schools in the state of Tocantins: Escola Municipal Rural Malhadinha, located in Comunidade Quilombola Malhadinha (Brejinho de Nazaré) and Colégio Estadual Fulgêncio Nunes (Chapada da Natividade). The object of the research was formed by students in the 8th and 9th year (Fulgêncio Nunes) and 3rd and 4th year (Malhadinha) of the Youth and Adults Education Program (corresponding to the 8th and 9 th years), and the Portuguese language and Quilombola Culture teachers. The pedagogical interventions were conducted by the literary literacy in the school, proposed by Cosson (2011) and were significant to raise the taste for literary reading in the school environment, offering the encounter with the literary texts of African Brazilian literature. The reading intervals contributed to the discussions about the works, approaching them towards motivation for reading, interpretation, expansion and contextualization. During those intervals, besides the aesthetical pleasure provided by the students’ involvement, a deeper discussion about identity and black culture raised, as well as its importance and statement for the strengthening of the black community and the traditional Quilombola ones. Such experience proved the statement that it is in the process of literary literacy, only access to books does not guarantee effectiveness in forming proficient readers and it is necessary to perpetuate a pedagogical practice which might link literary Reading to pleasure and to the refection about being in the world, favouring the creation of critical, empowered individuals.